Bulgaria's Policy for Regulatory Reform in the European Union : Converging with Europe's Best Regulatory Environments - World Bank (Washington, DC, 2013)
Bulgaria's entry into the EU Single Market raises new opportunities and new risks for the national economy. As shown in the rest of Europe, a program of regulatory reform offers an effective strategy for managing the risks of more intense competition while preparing Bulgarian companies to prosper within the largest economy in the world. Bulgaria has already made significant progress in regulatory reform, with an emphasis on developing regulatory impact analysis (RIA) in Bulgaria's public administration. To support these activities, the Council of Ministers agreed in August 2006 to the proposal of the Ministry of Economy and Energy to develop a national plan for better regulation. The goal is to progressively achieve a low-cost, low-risk regulatory system that both supports national competitiveness and effectively protects public interests. To achieve its potential, Bulgaria should converge, not with a minimum standard of regulatory reform, but with the best performers in Europe. This policy paper identifies nine tasks for setting up a modern regulatory system and meeting European obligations. These nine tasks are intended to improve the ability of the central government to promote regulatory reform, to build better regulation practices through the institutions of governments, and to improve the quality of both the stock and the flow of regulation on a permanent basis.